2023
DOI: 10.1186/s12877-022-03642-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between Clinical Frailty Scale (CFS) and clinical presentation and outcomes in older inpatients with COVID-19

Abstract: Background Frailty is a physiological condition characterized by a decreased reserve to stressors. In patients with COVID-19, frailty is a risk factor for in-hospital mortality. The aim of this study was to assess the relationship between clinical presentation, analytical and radiological parameters at admission, and clinical outcomes according to frailty, as defined by the Clinical Frailty Scale (CFS), in old people hospitalized with COVID-19. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Finally, in a subgroup of patients of the present cohort, the CFS calculation was obtained retrospectively by extrapolation of available data, in line with previous studies. 8,19 Nevertheless, the consistency and reliability of retrospectively calculated CFS may deserve further validation and our conclusions regarding the association of CFS with the clinical outcomes should be confirmed in prospective studies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Finally, in a subgroup of patients of the present cohort, the CFS calculation was obtained retrospectively by extrapolation of available data, in line with previous studies. 8,19 Nevertheless, the consistency and reliability of retrospectively calculated CFS may deserve further validation and our conclusions regarding the association of CFS with the clinical outcomes should be confirmed in prospective studies.…”
Section: Discussionmentioning
confidence: 80%
“…16 Frailty was assessed by the "Clinical Frailty Scale" (CFS), 17 based on the patients' condition 2 weeks before hospital admissions. If the CFS score was not recorded, in line with other previous studies, 18,19 our geriatric team retrospectively estimated CSF by review of specific electronic medical records, including medical and nursing notes, information about the physical function, and assistance required for feeding, washing, and dressing. The retrospective CFS assessment was validated for consistency and reproducibility by comparing it with the values calculated by two independent physicians, blinded to the geriatric team evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Symptoms such as productive cough, dyspnea, and delirium are significantly associated with COVID-19 mortality, emphasizing the need for immediate monitoring and intervention [ 56 ]. Laboratory tests show altered hematologic and biochemical markers in deceased patients, underscoring the importance of routine laboratory monitoring in COVID-19 patients [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that COVID‐19 patients who also have conditions like hypertension, diabetes, and obesity typically experience worse outcomes 55,57,58 . The body's capacity to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the immune system's normal function 59,60 …”
Section: Discussionmentioning
confidence: 99%
“… 55 , 57 , 58 The body's capacity to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the immune system's normal function. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%